Breeding success of the Black-throated Diver Gavia arctica inside and outside bird sanctuaries in Lakes Fegen and Sottern - Eriksson, Mats O G; Dahlgren, Tomas; Holmer, Arne; Lindberg, Peter; Åhlund, Matti (Ornis Svecica, 2005)
We compared the breeding success of Black-throated Divers Gavia arctica inside and outside bird sanctuaries with restricted public access during the incubation period in Lake Fegen-Svansjöarna and Lake Sottern, South Sweden. Both lakes held populations of approximately 15–20 pairs. At Fegen-Svansjöarna, average breeding success was 0.51 large chicks per pair and year inside and 0.27 outside the sanctuaries (field surveys in 1983—1984 and 1997—2000). The difference was not statistically significant, however, and in two out of the six study years breeding success was higher outside the bird sanctuaries. At Sottern, breeding success was 0.39 and 0.25 large chicks per pair and year inside and outside the bird sanctuary, but breeding success was higher inside the sanctuary only in four out of nine years, 1997—2005. The results from the two lakes together indicated an overall positive effect (P = 0.08). We recommend keeping a constant water-level during incubation to be the primary measure to enhance breeding success. Sanctuaries with limited access may be an additional benefit at lakes highly frequented for out-door recreation.